Accuracy of genomic selection predictions for hip height in Brahman cattle using different relationship matrices - Farah, Michel Marques [UNESP]; Fortes, Marina Rufino Salinas; Kelly, Matthew; Porto-Neto, Laercio Ribeiro; Meira, Camila Tangari [UNESP]; Carreño, Luis Orlando Duitama [UNESP]; da Fonseca, Ricardo [UNESP]; Moore, Stephen Stewart (FapUNIFESP (SciELO), 2018)
The objective of this work was to evaluate the effects of genomic information on the genetic evaluation of hip height in Brahman cattle using different matrices built from genomic and pedigree data. Hip height measurements from 1,695 animals, genotyped with high-density SNP chip or imputed from 50 K high-density SNP chip, were used. The numerator relationship matrix (NRM) was compared with the H matrix, which incorporated the NRM and genomic relationship (G) matrix simultaneously. The genotypes were used to estimate three versions of G: observed allele frequency (HGOF), average minor allele frequency (HGMF), and frequency of 0.5 for all markers (HG50). For matrix comparisons, animal data were either used in full or divided into calibration (80% older animals) and validation (20% younger animals) datasets. The accuracy values for the NRM, HGOF, and HG50 were 0.776, 0.813, and 0.594, respectively. The NRM and HGOF showed similar minor variances for diagonal and off-diagonal elements, as well as for estimated breeding values. The use of genomic information resulted in relationship estimates similar to those obtained based on pedigree; however, HGOF is the best option for estimating the genomic relationship matrix and results in a higher prediction accuracy. The ranking of the top 20% animals was very similar for all matrices, but the ranking within them varies depending on the method used.

O objetivo deste trabalho foi avaliar os efeitos da informação genômica na avaliação genética para altura do quadril em bovinos da raça Brahman, por meio de diferentes matrizes construídas com dados genômicos e de pedigree. Utilizaram-se medidas de altura do quadril de 1.695 animais, genotipados com SNP chip de alta densidade ou imputados do 50 K SNP chip de alta densidade. A matriz de pedigree numerator relationship matrix (NRM) foi comparada à matriz H, a qual incorporou as matrizes NRM e de parentesco genômico (G) simultaneamente. Os genótipos foram utilizados para estimar três versões de G: frequência observada dos alelos (HGOF), média da menor frequência alélica (HGMF) e frequência de 0,5 para todos os marcadores (HG50). Para a comparação das matrizes, foram utilizadas informações completas ou divididas em conjuntos de dados de calibração (80% dos animais mais velhos) e de validação (20% dos mais jovens). Os valores de acurácia para NRM, HGOF e HG50 foram 0,776, 0,813 e 0,594, respectivamente. NRM e HGOF foram semelhantes, com menores variâncias para os elementos da diagonal e fora da diagonal, bem como para os valores genéticos estimados. O uso de informações genômicas resultou em estimativas de parentesco semelhantes às obtidas com base em pedigree; entretanto, HGOF é a melhor opção para estimar a matriz de parentesco genômico e resulta em maiores acurácias de predição. O ranking dos animais top 20% foi muito semelhante para as matrizes, mas a classificação dentro destas varia dependendo do método.
Acurácia da predição genômica para altura do quadril em bovinos Brahman com uso de diferentes matrizes de parentesco
Keywords: alelos raros; Beef cattle; Bos indicus; Gado de corte; Genomics; Genômica; Rare alleles